Teaching Reading Comprehension through Anticipation Guides to the Eighth Grade Students of the State Junior High School 17 of Palembang - Ferry Hidayad (Universitas PGRI Palembang, 2018)
AbstractThe problem of this study, “Is it effective to teach reading comprehension Through Anticipation Guides to the eighth grade students of the State Junior High School 17 of Palembang?” Therefore the main objective of this study was to find out whether or not it is effective to use anticipation guides strategy in teaching reading comprehension. This study was done through the pre-experimental method with the one group pre-test and post-test design. The population of this study was 124 eighth grade students with 30 students as the samples which were chosen through convenience non random sampling. The technique used in collecting the data was a written test, pre-test and post-test. The data were analyzed through the formula of matched t-test.The result of this study indicated that after teaching reading comprehension through anticipation guides, the students’ mastery of reading comprehension improved. Their average level increased from the (6.32) to the (7.6). It was supported by the result of the data analysis that showed the t-obtained (9.14) which exceeded 1.697 as the critical value. It means that the Ho was rejected, and Ha was accepted. In other words, teaching reading comprehension through anticipation guides to the eighth grade students of the State Junior High School 17 of Palembang was significantly effective. Keywords: teaching, reading comprehension, anticipation guides